2019
DOI: 10.1038/s41598-019-50503-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Apparent Diffusion Coefficient in Hepatocellular Carcinoma Patients treated with Stereotactic Ablative Radiotherapy

Abstract: The role of diffusion-weighted magnetic resonance imaging (DW MRI) in assessing durable tumor control for patients with hepatocellular carcinoma (HCC) treated with stereotactic ablative radiotherapy (SABR) was not defined. This retrospective study included 34 HCC patients with 45 lesions who had DW MRI data at baseline and within 6 months post-SABR. On the first post-SABR MRI, 13 lesions (28.9%) had a complete response (CR), 12 (26.7%) had a partial response (PR), 17 (37.8%) had stable disease, and 3 (6.7%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Unlike the immediate post-treatment decreased-or non-enhancement following RFA and TACE, persistent arterial phase hyperenhancement for at least 12 months is common post SBRT and does not necessarily indicate viable neoplasm [25]. In addition to the mRECIST criteria, the AFP level as well as the apparent diffusion coefficient calculated from MRI sequences could improve the assessment of SBRT response and help to determine the LT candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the immediate post-treatment decreased-or non-enhancement following RFA and TACE, persistent arterial phase hyperenhancement for at least 12 months is common post SBRT and does not necessarily indicate viable neoplasm [25]. In addition to the mRECIST criteria, the AFP level as well as the apparent diffusion coefficient calculated from MRI sequences could improve the assessment of SBRT response and help to determine the LT candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported that a lower post-RT ADC indicates favorable outcomes in patients with glioma, 29,42 whereas an increased post-RT ADC is a favorable prognostic factor in patients with hepatocellular carcinoma. 43 This study suggests that HP 13 C MRI could provide information that is potentially unavailable from conventional 1 H multiparametric MRI.…”
Section: Discussionmentioning
confidence: 81%
“…This also agreed with Lo et al, who found that an ADC change of ≥25% within 6 months poststereotactic ablative radiotherapy (SABR) was an independent predictor of sustained HCC tumor control. The ADC values pre-and post-SABR were 1.43 ±0.28 x 10 -3 mm 2 /s and 1.72±0.34 x 10 -3 mm 2 /s respectively (p<0.001) [36] . This indicated that the ADC values could be established as a monitoring tool to assess the response of malignant lesions for treatment.…”
Section: Discussionmentioning
confidence: 85%